Local Government Financing Practice and Challenges in Developing Countries with Reference to Nepal - Sharma, Devilal (Journal of Political Science, 2021)
The fundamental problem confronting most local authorities, especially those managing cities in developing countries, is the widening gap between the availability of financial resources and municipal spending needs. One of the main reasons for this increasing fiscal gap is the rapid growth of urban populations, which creates an ever-increasing demand for public services, new public infrastructure, and its maintenance. Most cities in developing countries depend mostly on central government transfers, with lesser revenues derived from property taxation and service charges. The main aim of this study is to review the scholarly published documents regarding the responsible governing system of the local government in the developing economy and to observe the challenges to them to manage fiscal imbalances. Looking at the practice of fiscal federalism and economic decentralization, there is no uniformity in the global experience. Developed countries are at the forefront of this agenda while developing countries have different experiences. It is important to find the right path with the appropriate solution to the problem seen from the international experiment and move forward accordingly. It is important not only to make laws but also to achieve prosperous prosperity through their proper use and for that it is important to understand that the implementation of the law should be done in the right spirit.